1994
DOI: 10.1172/jci117371
|View full text |Cite
|
Sign up to set email alerts
|

Anti-nucleosome antibodies complexed to nucleosomal antigens show anti-DNA reactivity and bind to rat glomerular basement membrane in vivo.

Abstract: IntroductionHistones can mediate the binding of DNA and anti-DNA to the glomerular basement membrane (GBM). In ELISA histone/DNA/anti-DNA complexes are able to bind to heparan sulfate (HS), an intrinsic constituent of the GBM. We questioned whether histone containing immune complexes are able to bind to the GBM, and if so, whether the ligand in the GBM is HS. Monoclonal antibodies (mAbs) complexed to nucleosomal antigens and noncomplexed mAbs were isolated from culture supernatants of four IgG anti-nuclear mAb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
176
4
9

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(194 citation statements)
references
References 39 publications
5
176
4
9
Order By: Relevance
“…On the basis of the results presented above, serum antibodies and antibodies eluted from kidneys of individual B/W or BALB/c mice were further analyzed for binding to ␣-actinin, dsDNA, and H1. DNase I and heparan sulfate were included as control antigens in all ELISAs, because these ligands bind dsDNA (35) and nucleosomes (16,25).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the results presented above, serum antibodies and antibodies eluted from kidneys of individual B/W or BALB/c mice were further analyzed for binding to ␣-actinin, dsDNA, and H1. DNase I and heparan sulfate were included as control antigens in all ELISAs, because these ligands bind dsDNA (35) and nucleosomes (16,25).…”
Section: Resultsmentioning
confidence: 99%
“…It is unlikely that nucleosomes, if bound to these antibodies, could mediate binding to both anionic (DNA) and cationic (H1) structures. Nucleosomes are reported to bind anionic heparan sulfate or type IV collagen through protruding tails of cationic histones (16,25,38). In this respect, anti-dsDNA antibody-bound nucleosomes should be repelled by H1 rather than bound to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 High levels of nucleosomespecific Abs are often detectable in the serum of patients and young mice with lupus before the appearance of Abs to its individual components, dsDNA and histones (1,2). Nucleosomes are also important for mediating tissue lesions, especially glomerulonephritis (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Moreover, elevated plasma levels of nucleosomes have been observed in lupus patients (7,8), and a positive correlation (9,10) or absence of correlation (11) has been found between the level of these circulating nucleosomes and active disease. Compelling evidence is also accumulating to suggest that some (but not all) anti-nucleosome Abs are nephritogenic and that their level can be increased in active lupus (3,4,11,12). Amoura et al (11) further demonstrated an inverse correlation between nucleosome plasma levels and serum anti-nucleosome Ab activity.…”
mentioning
confidence: 99%